2019
DOI: 10.1088/1742-6596/1364/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Strapping Band Waste for Reviewed Mortar Againsts Compressive and Split Tensile Strength

Abstract: The aim of the study was to make mortar with a fiber mixture that utilizes band strapping waste. The selection of strapping band material as fiber since this material is not environmentally friendly, the benefits of this research can reduce band strapping waste and increase the economic value of band strapping waste. This research was conducted to determine the optimum fiber concentration value which resulted in the value of split tensile strength, compressive strength of maximum mortar, fiber strapping band w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Its because the original material used is plastic. The results of this study are inverse to research [5], [6], [7] that showed an increase in the compressive strength value of concrete on the use of fiber between 0% -1%, 5% and 9%.…”
Section: Fig 3 Compression Strength Values For 28 Days Ages Of Conccontrasting
confidence: 58%
See 2 more Smart Citations
“…Its because the original material used is plastic. The results of this study are inverse to research [5], [6], [7] that showed an increase in the compressive strength value of concrete on the use of fiber between 0% -1%, 5% and 9%.…”
Section: Fig 3 Compression Strength Values For 28 Days Ages Of Conccontrasting
confidence: 58%
“…The addition of materials to concrete usually aims to improve the characteristics of the concrete and the durability of concrete against certain fast conditions. Some added materials that can increase the compressive strength of concrete include palm fibers [2], PET plastic waste [3], broken glass [4], and waste strapping bands [5], [6], [7]. Prasetyo's research [5] the ratio of the strapping band fiber size increases the split tensile strength value of the SCC control concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation